Proteomic profiling of the rat renal proximal convoluted tubule in response to chronic metabolic acidosis - Freund, Dana Marie, author; Curthoys, Norman, advisor; Prenni, Jessica, advisor; Nyborg, Jennifer, committee member; Peersen, Olve, committee member; Dobos, Karen, committee member (Colorado State University. Libraries, 2013)
The human kidneys contain more than one million glomeruli which filter nearly 200 liters of plasma per day. The proximal tubule is the segment of the nephron that immediately follows the glomeruli. This portion of the nephron contributes to fluid, electrolyte and nutrient homeostasis by reabsorbing 60-70% of the filtered water and NaCl and an even greater proportion of NaHCO3. The initial or convoluted portion of the proximal tubule reabsorbs nearly all of the nutrients in the glomerular filtrate and is the site of active secretion and many of the metabolic functions of the kidney. For example, the proximal convoluted tubule is the primary site of renal ammoniagenesis and gluconeogenesis, processes that are significantly activated during metabolic acidosis. Metabolic acidosis is a common clinical condition that is characterized by a decrease in blood pH and bicarbonate concentration. Metabolic acidosis also occurs frequently as a secondary complication, which adversely affects the outcome of patients with various life-threatening conditions. This type of acidosis can occur acutely, lasting for a few hours to a day, or as a chronic condition where acid-base balance is not fully restored. Chronic metabolic acidosis, where the decrease in blood pH and bicarbonate last for 7 days, was the main focus of these studies. Acid-base homeostasis is achieved, in part, by the reabsorption of bicarbonate and excretion of ammonium ions and acids by the proximal convoluted tubule. Metabolic acidosis is partially compensated by an adaptive increase in renal ammoniagenesis and bicarbonate synthesis. During acidosis, there is increased extraction and mitochondrial catabolism of plasma glutamine within the renal proximal convoluted tubule. This process generates ammonium and bicarbonate ions that facilitate the excretion of acid and partially restore acid-base balance. This response is mediated by a pronounced remodeling of the proteome of the proximal convoluted tubule that also produces an extensive hypertrophy. Previous studies identified only a few mitochondrial proteins, including two key enzymes of glutamine metabolism, which are increased during chronic acidosis. Here, a workflow was developed to globally characterize the mitochondrial proteome of the proximal convoluted tubule. Two-dimensional liquid chromatography coupled with mass spectrometry (2D/LC-MS/MS) was utilized to compare mitochondrial enriched samples from control and chronic acidotic rats. Label-free quantitative strategies are commonly used in shot-gun proteomics to detect differences in protein abundance between biological sample groups. In this study we employed a combination of two such approaches, spectral counting (SpC) and average MS/MS total ion current (MS2 TIC). In total, forty nine proteins were observed to be significantly altered in response to metabolic acidosis (p-value < 0.05). Of these, 32 proteins were uniquely observed as significantly different by SpC, 14 by MS2 TIC, and only 3 by both approaches. Western blot analysis was used to validate the fold changes of eight of the proteins that showed an increase upon acidosis. Furthermore, using an antibody specific to acetylated lysine modifications indicated that chronic acidosis causes a 2.5 fold increase in this modification specifically in mitochondria. Western blot analysis established that the observed alterations in both protein abundance and lysine acetylation are not due to the associated hypertrophy. This study represents the first comprehensive analysis of whole mitochondrial proteome of the rat renal proximal convoluted tubule and its response to metabolic acidosis. Additionally, our analysis demonstrates an innovative dual approach for protein quantitation. To further our understanding of the impact of acidosis on the mitochondrial proteome, mitochondrial inner membranes were isolated from control and acidotic rat proximal convoluted tubules. Additional LC-MS/MS analysis was performed, representing the first proteomic characterization of the mitochondrial inner membrane proteome of the rat renal proximal convoluted tubule. Specific sites of lysine acetylation were identified both in the inner membrane and whole mitochondria, the majority of which are novel sites. The results presented here showed successful enrichment of mitochondrial inner membranes and described the proteins and the known biological processes of this compartment of the mitochondria. Previous proteomic analysis was performed on brush-border membrane vesicles isolated from proximal convoluted tubules from control, 1 d and 7 d acidotic rats. To validate the observed protein alterations, western blot analysis was performed on freshly isolated apical membrane. Additionally, the results from three independent proteomic studies focused on the apical membrane, mitochondrial, and soluble cytosolic fractions of the proximal convoluted tubules were compiled. Bioinformatics analysis was performed to describe predominate cellular processes and pathways that respond to chronic metabolic acidosis. The results of these studies demonstrate that the physiological response to the onset of metabolic acidosis requires pronounced changes in the renal proteome. The observed proteomic adaptations within the proximal convoluted tubule support the increased extraction of plasma glutamine and the increased synthesis and transport of glucose and of NH4+ and HCO3- ions. Overall, this dissertation describes the profiling of the proximal convoluted tubule proteome in response to chronic metabolic acidosis and provides the framework for future studies.
Keywords: kidney; proteomics; mitochondria; mass spectrometry; lysine acetylation; proximal convoluted tubule